2023
DOI: 10.1111/neup.12894
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of spinocerebellar ataxia type 8: Common features and unique tauopathy

Abstract: Spinocerebellar ataxia type 8 (SCA8) is a neurodegenerative condition that presents with several neurological symptoms, such as cerebellar ataxia, parkinsonism, and cognitive impairment. It is caused by a CTA/CTG repeat expansion on chromosome 13q21 (ataxin 8 opposite strand [ATXN8OS]). However, the pathological significance of this expansion remains unclear. Moreover, abnormal CTA/CTG repeat expansions in ATXN8OS have also been reported in other neurodegenerative diseases, including progressive supranuclear p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been confirmed that tauopathy was present in 2 cases of SCA8 autopsy, one of which exhibited 4-repeat tauopathy resembling PSP. 9 This finding reveals the complexity of SCA8 as a repeat expansion disease and highlights the necessity for further pathological research to elucidate the relationship between SCA8 and tauopathy.…”
Section: Discussionmentioning
confidence: 82%
“…It has been confirmed that tauopathy was present in 2 cases of SCA8 autopsy, one of which exhibited 4-repeat tauopathy resembling PSP. 9 This finding reveals the complexity of SCA8 as a repeat expansion disease and highlights the necessity for further pathological research to elucidate the relationship between SCA8 and tauopathy.…”
Section: Discussionmentioning
confidence: 82%
“…The neuropathology of SCA8 is unclear now, and the studies have revealed several shared characteristics in the affected individuals, including pronounced neuronal loss in the substantia nigra, loss of Purkinje neurons, atrophy of the molecular layer, and heightened proliferation of radial glia in the cerebellum (Yonenobu et al, 2023 ). Furthermore, polyglutamine monoclonal antibody 1C2-positive intranuclear inclusions and pan-nuclear staining were observed in the Purkinje, medulla, and dentate nucleus of the human SCA8 brain.…”
Section: Discussionmentioning
confidence: 99%
“…This condition, caused by pathogenic sequence variants in C19orf12 , was reported as a secondary tauopathy, as TAU pathology was reported by several studies [ 253 255 ]. Recently, TAU pathology was observed in some cases of spinocerebellar ataxia type 8 (SCA8), a condition caused by abnormal CTA/CTG repeat expansions in ATXN8OS which have also been reported in PSP [ 256 ]. However, a precise pathomechanistic connection to TAU has not yet been established in these cases.…”
Section: Secondary Tauopathiesmentioning
confidence: 99%